Persalinan pada Ibu Berusia Kurang dari 20 Tahun di RSUD Kabupaten Buleleng - Ketut Eka Larasati Wardana; Agus Ari Pratama; Luh Yenny Armayanti (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Background: Pregnancy with less than 20 years of age is an important problem because it belongs to the high risk group. This is related to the increased risk of maternal complications during pregnancy and childbirth, as well as in the perinatal. From the preliminary study, the incidence of maternity mothers aged less than 20 years old at Buleleng Regency Hospital in 2021 was 7.3%. Purpose: The purpose of the study was to look at the picture of childbirth in mothers less than 20 years old. Method: This study used descriptive methods with a sample of all babies born to maternity mothers aged less than 20 years at Buleleng Regency Hospital for the period September - December 2021 as many as 236 study subjects. Results: The results of this study obtained an average maternal age of 17.2 years, an average gestational age of 36.9 weeks, an average birth weight of 2791.2 grams, a 1 minute 72% normal Apgar score, a 5-minute Apgar score of 76.7% normal, no incidence of congenital abnormalities, a stillbirth event of 4.2%, the distribution of events based on maternal age is more found in the mother's age is more found in the mother group aged 16-19 years. Conclusion: There are still many pregnancies in mothers less than 20 years old, there is no incidence of congenital abnormalities, still the incidence of stillbirth.